Behaviors of capacitive and Pirani vacuum gauges: Case study on time effect - Zavarian, Ali Asghar; Arman, Ali; Ghotbi, S. M. Jamal; Korpi, Alireza Grayeli; Salehi, Maryam; Mardani, Mohsen; Hafezi, Fatemeh; Shafiekhani, Azizollah; Ţălu, Ştefan; Afghan, Ashkan Sepehr (Vakuum in Forschung und Praxis : Zeitschrift für Vakuumtechnologie, Oberflèachen und Dünne Schichten, 2018)
Knowing the exact pressure of the process has a great impact on the validity of the results, product quality, energy efficiency, and in some processes, on the security of work with the system. Hence, the calibration of the barometers and the accuracy of the readings should be taken seriously. Choosing the appropriate time interval for re‐calibration is done according to the extent and conditions of use, uncertainty, and the inaccuracy allowed in measurement, constructive suggestion, and some other things. Failure to pay attention to the importance of periodic calibration in vacuum gauges leads to some irreparable losses in the research project and the vacuum generator system. In this study, using McLeod's barometer, the deviation of capacitive and Pirani vacuum gauges is investigated at different time intervals in the middle vacuum range, and it is determined that the vacuum gauge faces a serious deviation from the actual calibrated amount for upper and lower ranges of middle vacuum in the same working pressure range over time. Verhalten von kapazitiven und Pirani‐Druckmessgeräten – Eine Fallstudie zum Thema Zeiteffekt Die Kenntnis des genauen Drucks eines Prozesses hat einen groẞen Einfluss auf die Aussagekraft der Ergebnisse, die Qualität der Produkte, die Energieeffizienz des Verfahrens und in einigen Prozessen auch auf die Sicherheit während der Arbeit mit dem System. Daher sollte die Kalibrierung der Messgeräte und die Genauigkeit der Messwerte ernst genommen werden. Die Wahl des geeigneten Zeitintervalls für die Neukalibrierung erfolgt in Abhängigkeit von Umfang und Einsatzbedingungen sowie von zulässigen Messabweichung, baulichen Vorgaben und einigen anderen Faktoren. Die Vernachlässigung regelmäẞiger Kalibrierungen von Vakuummessgeräten kann zu nicht behebbaren Verlusten in Produktion und Forschungsvorhaben führen. In dieser Studie werden für den mittleren Vakuumbereich mit Hilfe eines McLeod‐Barometers die Abweichungen von kapazitiven und Pirani‐Vakuummessgeräten in verschiedenen Zeitabständen untersucht. Es konnte festgestellt werden, dass Vakuummessgeräte im Laufe der Zeit gravierende Abweichungen in Hinblick auf die tatsächlich eingemessene Gasmenge aufweisen.